Nutritional evaluation of soy yoghurt in comparison to soymilk and commercial milk yoghurt. Effect of fermentation on soy protein - Silva Júnior, S.; Tavano, O.; Demonte, Aureluce [UNESP]; Rossi, Elizeu Antonio [UNESP]; Pinto, R. [UNESP] (Akademiai Kiado Zrt., 2012)
Soymilk was fermented using Lactobacillus delbrueckii ssp. bulgaricus and Streptococcus thermophilus. The soy yoghurt produced was evaluated in comparison to soymilk and commercial milk yoghurt by biological evaluation, rat growth, nitrogen balance assays and microbiological methods. Trypsin inhibitor activity and chemical composition were also determined for all samples. For the soy yoghurt, the growth and nitrogen balance values were not different from the control diet, but the nitrogen balance values were higher than for the soymilk, without significant difference in terms of growth assays. Compared to the commercial yoghurt, Net Protein Ratio and Nitrogen Utilization values were lower, but the Protein Efficiency Ratio, Biological Value and Net Protein Utilization values were equivalent, and for digestibility assays the best results were obtained with the soy yoghurt. The results indicated that soy yoghurt represents a good protein alternative to milk yoghurt and casein. The protein quality of soymilk evidently increased during the fermentation process using Lactobacillus delbrueckii ssp. bulgaricus and Streptococcus thermophilus, including a reduction in trypsin inhibitor levels of about 30%.
Keywords: digestibility; nutritional evaluation; protein quality; soy fermented; soymilk; yoghurt; Glycine max; Lactobacillus delbrueckii; Rattus; Streptococcus thermophilus